Self‐Assembly of ZnII/CdII/PbII Coordination Polymers with a Tripodal Ligand Derived from Aromatase Inhibitor Letrozole Derivative - Si, Jin‐Ping; Wang, Wen‐Jing; Chang, Jun; Huang, Kun‐Lin; Zhang, Zhi‐Hui; Chen, Sheng‐Chun; He, Ming‐Yang; Chen, Qun (Zeitschrift für anorganische und allgemeine Chemie (1950), 2020)
Reactions of the aromatase inhibitor letrozole derivative 4,4'‐(1H‐1,2,4‐triazol‐1‐yl)methylene‐bis(benzonic acid) (H2tzmb) with ZnII, CdII, or PbII salts under similar conditions resulted in the generation of three coordination polymers, namely, {[Zn(tzmb)(H2tzmb)]·H2O}n (1), [Cd(tzmb)(H2O)2]n (2), and {[Pb(tzmb)(H2O)]·DMF}n (3), respectively. Their structures were determined by single‐crystal X‐ray diffraction analyses and further characterized by elemental analysis, IR spectroscopy, powder X‐ray diffraction, and thermogravimetric analyses. Complex 1 features a twofold 2D → 2D interpenetrated network based on corrugated 63‐hcb layers, and complex 2 exhibits a flat 2D 4.82‐fes network, whereas complex 3 presents a 3D hex net based on infinite rod‐shaped secondary building units. The remarkable structural diversity may illustrate the powerful effect of metal ions on coordination assemblies. The spectroscopic, thermal, and photoluminescent properties of complexes 1–3 were investigated. In addition, the catalytic activity of 1 in the solvent‐free ring‐opening polymerization of ε‐caprolactone was also discussed.